PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA ELEMEN BHINNEKA TUNGGAL IKA MENGGUNAKAN MODEL PROBLEM BASED LEARNING DI KELAS IV SD NEGERI 05 AIR TAWAR BARAT KOTA PADANG - Hazmi, Merinda; Anita, Yesi; Waldi, Atri; Kharisma, Inggria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the low learning outcomes of students in Pancasila Education, particularly in the Bhinneka Tunggal Ika element. This problem is caused by teacher-centered learning, limited student participation, and the lack of innovative learning models. This study aims to describe the improvement of students' learning outcomes through the implementation of the Problem Based Learning (PBL) model in Grade IV of SD Negeri 05 Air Tawar Barat, Padang City. This research is a Classroom Action Research (CAR) using qualitative and quantitative approaches. It was conducted in two cycles consisting of planning, implementation, observation, and reflection. Data were collected through observation, tests, and non-test techniques. The subjects were the classroom teacher, the researcher, and 23 fourth-grade students. The results showed that the teaching module improved from 89.55% (Good) in cycle I to 95.8% (Very Good) in cycle II. The teacher’s and students’ implementation aspects increased from 91% to 96.4% (Very Good). Students’ learning outcomes also improved from an average score of 81.32 (Good) in cycle I to 93.37 (Very Good) in cycle II. It can be concluded that the Problem Based Learning (PBL) model effectively improves students' learning outcomes in Pancasila Education, especially in the Bhinneka Tunggal Ika element.